Generic Inference : A Unifying Theory for Automated Reasoning - Pouly, Marc, 1980-; Kohlas, Jurg, 1939- (Hoboken, New Jersey : Wiley, 2011)
'This book provides a rigorous algebraic study of the most popular inference formalisms with a special focus on their wide application area, showing that all these tasks can be performed by a single generic inference algorithm. Written by the leading international authority on the topic, it includes an algebraic perspective (study of the valuation algebra framework), an algorithmic perspective (study of the generic inference schemes) and a'practical' perspective (formalisms and applications). Researchers in a number of fields including artificial intelligence, operational research, databases and other areas of computer science; graduate students; and professional programmers of inference methods will benefit from this work'--
'The book provides a rigorous algebraic study of the most popular inference formalisms with a special focus on their wide application area and shows that all these tasks can be performed by a single generic inference algorithm. It will include an algebraic perspective (study of the valuation algebra framework), an algorithmic perspective (study of the generic inference schemes) and a'practical' perspective (formalisms and applications)'--
Includes bibliographical references (pages 437-446) and index.
Keywords: Valuation theory; Algorithms; Algebra, Abstract